Les représentations mémorielles de la guerre civile grecque dans le discours des vainqueurs et des vaincus - Christina Alexopoulos (Amnis, 2015)
The representations of the Greek Civil War in the discourses of the conflict's winners and losers interrogate the reconstruction of a past that divides not only the specular relationship of two opposed discursive realities within the principal communities of memory, but also the limits of these symmetrical phenomena, in relationship with the synchrony of enunciation and the diachrony of the evolution of the systems of reference being studied.